2023
DOI: 10.1111/tpj.16391
|View full text |Cite
|
Sign up to set email alerts
|

How metabolism and development are intertwined in space and time

Abstract: SUMMARYDevelopmental transitions, occurring throughout the life cycle of plants, require precise regulation of metabolic processes to generate the energy and resources necessary for the committed growth processes. In parallel, the establishment of new cells, tissues, and even organs, alongside their differentiation provoke profound changes in metabolism. It is increasingly being recognized that there is a certain degree of feedback regulation between the components and products of metabolic pathways and develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 138 publications
(191 reference statements)
0
0
0
Order By: Relevance
“…Although most plants show a pronounced apical growth dominance, lateral organ formation is inducible and highly sensitive to the plant’s sugar status ( 6 , 9 ). However, how metabolism and development are coordinated is far from being understood ( 38 ). Recent work demonstrated that rapid sugar reallocation to dormant axillary rosette branches upon decapitation acts as an initial trigger for bud outgrowth ( 5 ) and highlights the impact of sugar signaling on shoot branching ( 39 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although most plants show a pronounced apical growth dominance, lateral organ formation is inducible and highly sensitive to the plant’s sugar status ( 6 , 9 ). However, how metabolism and development are coordinated is far from being understood ( 38 ). Recent work demonstrated that rapid sugar reallocation to dormant axillary rosette branches upon decapitation acts as an initial trigger for bud outgrowth ( 5 ) and highlights the impact of sugar signaling on shoot branching ( 39 42 ).…”
Section: Discussionmentioning
confidence: 99%